Antibacterial Activity Test of Kersen Fruit Kombucha ( Muntinga Calabura L. ) To Bacteria Staphylococcus Aureus and Escherichia Coli By In Vitro - arikha ayu susilowati (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Bacterial infections of Staphylococcus aureus and Escherichia coli cause diarrhea. Kersen fruit can be used as the basis of kombucha, which has antibacterial benefits. This experimental activity aims to determine the antibacterial activity against Escherichia coli and Staphylococcus aureus. This study used a laboratory experimental method to test the antibacterial activity of Kersen Fruit Kombucha (KFK) at concentrations of 15%, 25%, and 35%, as well as positive control of cotrimoxazole and normal control of aqua pro injection. Antibacterial activity was measured in vitro using the disc diffusion method to compare affected and unaffected areas. The results of the study on Escherichia coli and Staphylococcus aureus bacteria showed that the diameter of the inhibition zone in 15% KFK was 7.07-8.63 mm, 25% KFK showed an inhibition zone diameter of 8.11-9.57 mm; and 35% KFK inhibition zone diameter was 12.07-13.07 mm; for the positive control inhibition zone diameter was 13.07-14.72 mm. 35% KFK has a larger inhibition zone diameter than 15% and 25% KFK. Based on the Kruskal-Wallis statistical test, there was a significant difference. This study aims to determine the antibacterial activity of Kersen fruit kombucha against Staphylococcus aureus and Escherichia coli by measuring the diameter of the inhibition zone